Perhitungan Premi Risiko Asuransi Kendaraan Bermotor Berdasarkan Data Frekuensi dan Besar Klaim - Dwi Sekar Kania; Aceng Komarudin Mutaqin (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Risk is an unpleasant result (harm) of an action or action. Life insurance is a risk transfer effort that bears financial losses from the risk of the death of the policyholder. General insurance is a risk transfer effort that insures property that may suffer losses. The product of general insurance is motor vehicle insurance. The number of motorized vehicles indicates how useful motorized vehicles are, which causes an increase in motorized vehicle ownership. In line with that, the incidence of road accidents is also increasing, but many of those who suffer losses from vehicle accidents do not receive the compensation that is the right of the vehicle owner. From the explanation of insurance, it is said to be able to control a risk, where in insurance we have to pay a certain amount of money to get the